Formation and biodegradation of toluene in the anaerobic sludge digestion process - Mrowiec, Bozena (Water environment research : a research publication of the Water Environment Federation, 2005)
The formation of toluene in municipal anaerobic primary and secondary sludge digestion processes was investigated. Experiments were carried out in a large laboratory-scale reactor using sludge from a primary settling tank of a municipal treatment plant. It was found that toluene was produced in the supernatant in relatively large concentrations for almost all cases tested. The concentration of toluene varied and was found to depend on the stage of the anaerobic process. During the acidity phase, which is the first stage of anaerobic digestion, an increase of toluene concentration was observed, while in the transition period, from the acidity phase to methanogenesis, the toluene concentration decreased. It was concluded that biosynthesis of toluene occurs in the acidogenic phase, while biodegradation was prevalent in the methanogenic stage. Depending on the type of experiments, an increase of toluene from a base value of approximately 200 microg/L up to 20,000 and 42,000 microg/L was measured in the first stage of anaerobic digestion. In the subsequent methane-production stage of digestion, the estimated rate of toluene decrease (biodegradation) varied from 400 to 900 microg/L-d